2017
DOI: 10.1074/jbc.m116.772442
|View full text |Cite
|
Sign up to set email alerts
|

Determination of dendritic spine morphology by the striatin scaffold protein STRN4 through interaction with the phosphatase PP2A

Abstract: Dendritic spines are heterogeneous and exist with various morphologies. Altered spine morphology might underlie the cognitive deficits in neurodevelopmental disorders such as autism, but how different subtypes of dendritic spines are selectively maintained along development is still poorly understood. Spine maturation requires spontaneous activity of -methyl-d-aspartate (NMDA) receptor and local dendritic protein synthesis. STRN4 (also called zinedin) belongs to the striatin family of scaffold proteins, and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 66 publications
0
31
0
Order By: Relevance
“…In addition, CTTNBP2 is also found to regulate the synaptic distribution of striatin 4 (STRN4) and zinedin, which are the regulatory B subunits of protein phosphatase 2A (PP2A), suggesting that CTTNBP2 targets the PP2A complex to dendritic spines, and together with cortactin regulate spine morphogenesis and synaptic signaling 36,44 . The involvement of these proteins in autism has been speculated 45 , and in support of this, the human STRN4 gene is located in chromosome 19q13.32, which is the locus for a reported deletion in ASD 46 .…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…In addition, CTTNBP2 is also found to regulate the synaptic distribution of striatin 4 (STRN4) and zinedin, which are the regulatory B subunits of protein phosphatase 2A (PP2A), suggesting that CTTNBP2 targets the PP2A complex to dendritic spines, and together with cortactin regulate spine morphogenesis and synaptic signaling 36,44 . The involvement of these proteins in autism has been speculated 45 , and in support of this, the human STRN4 gene is located in chromosome 19q13.32, which is the locus for a reported deletion in ASD 46 .…”
Section: Accepted Manuscriptmentioning
confidence: 82%
“…Only a few other research groups have addressed the role of PP2A in DS formation. Li et al [51] recently indicated that PP2A is necessary for DS formation in striatal neurons [52]. Liu et al [53] determined that PP2A interacts with the protein PRG-1 at the postsynaptic density not only to modulate synaptic plasticity but also to produce the recruitment of focal adhesion proteins such as Src and paxillin.…”
Section: Discussionmentioning
confidence: 99%
“…The rs10409124 is located on the 13th exon of STRN4, resulting in a substitution of valine by isoleucine at site 568. STRN4 maps at 19q13.2 and is involved in protein domain-specific binding and calmodulin binding (Lin et al, 2017). STRN4 belongs to the striatin family of scaffold proteins that are highly expressed in the nervous system and are also known to form complexes with protein phosphatases and protein kinases (Wong et al, 2014).…”
Section: Discussionmentioning
confidence: 99%